AMTSILATI METHOD IMPLEMENTATION IN PESANTREN AL-AQOBAH KWARON JOMBANG - Wicaksono, Arif (Journal Of Islamic Education And Pesantren, 2021)
The purpose of this study was to determine the implementation of the amtsilati method at the Al-Aqobah Kwaron Islamic Boarding School, Jombang. This study concludes several points. First, the implementation of the Amtsilati Method at the Al-Aqobah Kwaron Diwek Jombang hut begins with mapping, namely: a) The first year of memorizing the rules of nahwu and sharaf science and understanding the five volumes of the Amtsilati book; b) The second year of implementing the Amtsilati method when reading a book that has been determined by the ustadz; c) The third year of reading, understanding the content of the yellow book with reference to the Amtsilati method. Second, the obstacle and solution in implementing the amtsilati method to accelerate the ability to read the yellow book at the Al-Aqobah Kwaron Diwek Jombang boarding school is the obstacle that students experience boredom when memorizing and understanding the Amtsilati method because of the different experiences of students before boarding and studying the yellow book. The solution is to add training so that those who are still left behind in the material can catch up with those who already understand giving lessons to those who cannot. Keywords: amtsilati method, turath, pesantren. IMPLEMENTASI METODE AMTSILATI DI PONDOK PESANTREN AL-AQOBAH KWARON JOMBANG Abstrak Tujuan penelitian ini adalah untuk mengetahui implementasi metode amtsilati di pondok pesantren al-aqobah kwaron jombang. Penelitian ini menyimpulkan beberapa poin. Pertama, Implementasi Metode Amtsilati di pondok Al-Aqobah Kwaron Diwek Jombang diawali dengan pemetaan yaitu: a) Tahun pertama menghafalkan qaidah ilmu nahwu dan ilmu sharaf dan memahami lima jilid kitab Amtsilati; b) Tahun kedua mengimplementasikan metode Amtsilati ketika membaca kitab yang telah ditentukan oleh ustadz; c) Tahun ketiga membaca, memahami kandungan kitab kuning dengan acuan metode Amtsilati. Kedua, Kendala dan solusi dalam implementasi metode amtsilati untuk mempercepat kemampuan membaca kitab kuning di pondok Al-Aqobah Kwaron Diwek Jombang adalah Kendala para santri mengalami kejenuhan ketika menghafal dan memahami metode Amtsilati karena pengalaman santri yang berbeda sebelum mondok dan belajar kitab kuning. Solusinya adalah penambahan latihan supaya yang masih tertinggal materi bisa menyusul yang sudah faham memberi pengajaran kepada yang belum bisa. Kata kunci: metode amtsilati, turath, pesantren.